THE EFFECT OF PRICE AND FREE SHIPPING TAGLINE ON PURCHASE DECISION AT E-COMMERCE SHOPEE (STUDY ON ALUMNI OF SMAN 13 BANDUNG) - Erpurini, Wala; Muhammad Rifky Pratama; Irma Devita Haryono (SEAN Institute, 2022)
This research was conducted on Shopee users at SMAN 13 Bandung alumni. The purpose of this research is to find out how much the price and free tagline contribute to purchasing decisions, either partially or simultaneously at Shopee. The research method that will be carried out in this research is descriptive method and associative method. In this study, the unit of analysis is the individual, namely the alumnus of Shopee SMAN 13 Bandung. The sample in this study were 125 respondents. Sampling using judgment sampling. The analytical method used is multiple linear regression analysis, in addition to testing the validity and reliability of the research instrument. Based on the results of the study indicate that there is a partial or simultaneous influence of price and tagline variables on purchasing decisions. The implication of this research is that Shopee can maintain price variations to compete with other e-commerce and realize the free shipping tagline so that consumers decide to buy at Shopee e-commerce.